Transformasi Ekonomi Zakat: Penerima Menjadi Wajib Zakat - Hamzah Hamzah; St. Umrah St. Umrah (Jurnal Al-Mizan, 2020)
This research aims to elaborate the utilization of zakat and the development of amil in the concept of transformative leadership. The type of research used is library research. The data source in this study consists of 8 books, 4 journals and 8 internet sites related to information on zakat economic transformation. The method is using content analysis techniques to discuss results. The results of the study indicate that amil has a strategic role in the transfer of knowledge to the recipients of zakat in the context of making use of zakat as community empowerment. Schermerhor's view is used in the development of amil in realizing transformative leadership. The impact of the amil transformative leadership model can transform the mustahik of zakat into the muzakki of zakat.